Juventude, trabalho e educação superior: a geração y em análise - Borges, Bento Souza (2014)
Nowadays, it is increasingly common the inflow of youngsters of a very low age into college education in Brazil. These young people bring with them a number of very peculiar characteristics which previous generations did not have, caused in part by the technological revolution starting in the 1970s. They grew up at a time of great technological advancement and economic prosperity. This new Generation, known as Generation Y, leads an everyday life with people from other generations in the workplace and at school. Most of the time, the previous generations did not have or still do not have the same technological intimacy and did not develop the same habits of Generation Y, that grew up among hectic action, being stimulated by various activities and performing multiple tasks. The studies which approach issues related to generational matter and specifically Generation Y does have some controversies such as the starting point, for some, since 1977, for others since 1985. As to Generation Y behavior, some describe them as well-behaved, team workers and ethicists and others as self-centered, superficial and rebels. Some authors refer to these youngsters as digital natives, and to people of other previous generations as digital migrants. With so many changes in the profile of these young people, it is natural that the school environment has to undergo some modifications to adapt to this new era: new student and new worker. Considering that these young people are at the same time fruit of this technological time and active agents of this process of change, we understand that both the school environment and the work carried out by the teacher is undergoing profound transformations to meet the needs of a new public with such distinctive features. Thus, this paper aims to broaden the debate about Generation Y and assess the influences of the Technological Revolution occurred on these young people in labor relations, and especially in the school environment and on the teaching work. To achieve that, we sought some grounding in theories of work and in studies on youth and generations and management, and some theorists in the area of college education, always taking into account the philosophical, sociological and educational aspects to analyze this Generation. Through a bibliographic research, we realized that changes in the world regarding technological developments and globalization have influenced much the character, ideals and behavior of the young people and this is directly reflected in school. The teacher needs to know how this new Generation thinks and acts, and then seek new teaching practices that are consistent with this audience. What we cannot fail to understand is that the changes brought about by the arrival of Generation Y are not passing. As more and more young people come to school age and later to the labor market and assume leadership positions, the schools and enterprises need to adapt themselves to this vibrantly connected and restless Generation.